Dedication: Close reading: Ludi Schulze and Calvin research - Erik A. de Boer (Acta Theologica)
From text: How should we paint a picture of a scholar who in the course of a lifelong career has become well known to the South-African academic community? In some universities their professor emeritus was honoured by a painting of his torso and learned head, hung on the wall of their own “hall of fame”. In the modern era of snapshots and budget cuts a photo is often the only remaining tribute. It might be worthwhile to draw a picture of Prof. Dr. L.F. Schulze, so that also the younger generations have a chance to become acquainted with him.